2020
DOI: 10.1001/jamanetworkopen.2019.18634
|View full text |Cite
|
Sign up to set email alerts
|

Association of Deceased Donor Acute Kidney Injury With Recipient Graft Survival

Abstract: IMPORTANCE The shortage of deceased donor kidneys for transplants is an ongoing concern. Prior studies support transplanting kidneys from deceased donors with acute kidney injury (AKI), but those investigations have been subject to selection bias and small sample sizes. Current allocation practices of AKI kidneys in the United States are not well characterized. OBJECTIVES To evaluate the association of deceased donor AKI with recipient graft survival and to characterize recovery and discard practices for AKI k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(101 citation statements)
references
References 52 publications
3
88
1
Order By: Relevance
“…However, there is now considerable evidence that AKI is often reversible and that kidneys from donors with AKI provide short‐ and long‐term graft survival and function comparable to kidneys with nonelevated terminal creatinine 37,40‐46 . Liu et al’s 47 recent comparison of propensity score‐matched deceased donors with AKI to deceased donors without AKI demonstrated that deceased donor AKI had no independent association with short‐term and long‐term recipient graft survival across all AKI stages. Although elevated creatinine in the setting of chronic kidney disease (CKD) in the donor would be a justifiable reason for nonprocurement, severe kidney disease may also preclude procurement of nonrenal organs such as heart and lungs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is now considerable evidence that AKI is often reversible and that kidneys from donors with AKI provide short‐ and long‐term graft survival and function comparable to kidneys with nonelevated terminal creatinine 37,40‐46 . Liu et al’s 47 recent comparison of propensity score‐matched deceased donors with AKI to deceased donors without AKI demonstrated that deceased donor AKI had no independent association with short‐term and long‐term recipient graft survival across all AKI stages. Although elevated creatinine in the setting of chronic kidney disease (CKD) in the donor would be a justifiable reason for nonprocurement, severe kidney disease may also preclude procurement of nonrenal organs such as heart and lungs.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] However, there is now considerable evidence that AKI is often reversible and that kidneys from donors with AKI provide short-and long-term graft survival and function comparable to kidneys with nonelevated terminal creatinine. 37,[40][41][42][43][44][45][46] Liu et al's 47 This study has several limitations. We rely on OPTN registry data, which may contain reporting errors.…”
mentioning
confidence: 88%
“…Donors’ serum creatinine also had to be within normal range at the time of the organ procurement, so kidneys from donors with acute kidney injury (AKI) were discarded even if they had no substantial comorbidities, and so were kidneys from donors with a history of hypertension but no evidence of any organ damage. There is growing evidence of donated kidneys with AKI achieving much the same long‐term renal function and graft survival rates as those without AKI [15]. Donors with mild hypertension well controlled with antihypertensive medication, and no evidence of organ damage is now considered suitable, not expanded criteria donors [16].…”
Section: Focus On Deceased Donor‐initiated Chainsmentioning
confidence: 99%
“…Several researches have recently been published regarding the clinical impact of KT from deceased donors (DDs) with acute kidney injury (AKI) in deceased donor KT (DDKT) [ 12 , 13 ]. AKI is very commonly detected in individuals with brain death state for various causes [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%